PSYCHOSOCIAL DEVELOPMENT THROUGH TRADITIONAL GAMES AND SPORTS IN ELEMENTARY SCHOOL STUDENTS - Julianti, Rekha Ratri; Suherman, Adang; Ma'mun, Amung; Budiana, Dian; Zinat Ahmad, Irfan; Purwanto, Setyo (JUARA : Jurnal Olahraga, 2024)
The purpose of this study was to determine the formation of psychosocial through traditional games and sports. Various traditional games and sports activities such as clogs, boy-boyan, cat-mouse, hopscotch, gobak sodor, snakes and ladders and stilts can create things that arouse students' social attitudes. This creates a learning experience to be able to train teamwork, goal setting, psychosocial adjustment needs and psychosocial adjustment needs from social relationships. This study used an experimental method with a pretest and posttest design with a sample of 25 elementary school students. The results showed that there was a significant influence on increasing psychosocial in the sample given the traditional games and sports program.